Online Lectures on Learning Achievement at Student of Guidance Counseling (Subject Personal Development Counselor) and Physical Education (Subject Sports Health) - Ladjar, Maria Andriani Barek; Korohama, Katharina Edeltrudis Perada (Universitas Negeri Semarang, 2021)
Almost a year, Indonesia is in a situation that is quite complicated, due to the spread of covid-19 significantly in many areas, it is then compounded by the numbers died fairly high. Governments and health workers have always called people to always maintain a healthy lifestyle and clean, to avoid the spread of this virus. From its appearance to a pattern of adaptation that has been done many, covid-19 directly has affected and changed the system order of human life in all sectors, not least in the world of education. In this pandemic period, various factors emerged in their own way which greatly influenced the system and even the habit patterns of learning activities. After approximately 1 year running, online lecturing has become a habit that occurs in learning, so it also affects learning achievement. Therefore, this research will look at the extent to which the online lecture process carried out in the current year also affects the learning achievement of students of the BK Study Program and the Penjaskesrek Study Program, FKIP, Undana Kupang. The conclusions obtained: (1) There is a significant effect of online lectures on student achievement of Counseling Guidance students and (2) There is a significant effect of online lectures on student learning achievement of Penjaskesrek.